Electroencephalographic power spectrum changes in cerebral small vessel disease combined with cognitive dysfunction and its relationship with neutrophil/lymphocyte ratio and its clinical value – a pilot study - Guo, Xiaomin; Liu, Zongwei; Yuan, Weishuai; Wei, Aiqin; Luo, Guogang (Frontiers in Neurology, 2024)
Objective: To explore the changes in the electrical power spectrum of the brain and its correlation with neutrophil/lymphocyte ratio (NLR) in patients with cognitively impaired cerebral small vessel disease (CSVD) and to explore its clinical application.Methods: A total of 61 patients with CSVD who attended the People's Hospital of Shaanxi Province from September 2021 to September 2022 were divided into the group with cognitive impairment (Cerebral small vascular with cognitive impairment, CSVCI group, n = 29) and the group without cognitive impairment (CSVD group, n=32) based on the Montreal Cognitive Assessment Scale (MoCA) score. While 20 healthy subjects were recruited as the control group (healthy control, HC group). EEG was performed in the three groups, and the difference in whole brain quantitative EEG power spectral density (PSD) was calculated and compared between the three groups.Results: The PSD values in the δ and θ bands of the CSVCI group were higher than those of the CSVD group, while the PSD values in the α band were lower than those of the CSVD and HC groups. In addition, PSD values in the δ-band in the CSVD group were lower than those in the HC group (all P < 0.05). Multifactorial logistic regression showed that reduced α-band global average PSD and low years of education were independent risk factors for cognitive impairment in patients with CSVD (P < 0.05). In patients with cerebral small-vessel disease, α-band PSD was positively and δ-band PSD negatively correlated with MoCA socre, and paraventricular, deep white matter, and total Fazekas scores were negatively correlated with MoCA socre. Furthermore, θ-band PSD is positively correlated with NLR (all P < 0.05).Conclusions: EEG activity was slowed down in patients with CSVD with cognitive impairment. The α-band global mean PSD values independently affected the occurrence of cognitive impairment inCSVD patients beyond the Fazekas score. NLR may be one of the mechanisms leading to the slowing down of the EEG, which can be used as an objective indicator for the early prediction of cognitive impairment, but still needs to be clarified by further studies.